Empirical analysis of non-financial reporting by Spanish companies - Laura Sierra-Garcia; Maria Antonia Garcia-Benau; Helena Maria Bollas-Araya (Administrative Sciences, 2018)
Spain is one of the European countries that is the most strongly committed to the presentation of non-financial information. In 2017, Spain adapted its legislation to Directive 2014/95/EU through Royal Decree-Law 18/2017, which required Public Interest Entities (PIEs) to provide information in accordance with the requirements of the European Union (EU) Directive, with respect to financial years from 1 January 2017. Our research is focused on Spanish IBEX-351 listed companies and seeks to identify current trends in non-financial reporting. To our knowledge, the present paper is the first study to examine the impact made in Spain by the legislative changes. Our aim is to analyse the publication of non-financial information by Spanish listed companies whose first reports in this regard were made from early 2018. Specifically, we consider the impact of this information disclosure, determining whether the companies in question restrict themselves to meeting regulatory requirements or whether they go further and voluntarily supply additional information. Our findings show that the level of regulatory compliance produced is associated with the business sector in which the company operates. We also show that the highest rates of disclosure of non-financial information correspond to companies that provide this information in the sustainability report.
Keywords: 350; non-financial information; non-financial report; sustainability report; Directive 2014/95/EU